2010
DOI: 10.1177/1545968310380926
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Environment Improves Motor Function and Increases Neurotrophins in Hemicerebellar Lesioned Rats

Abstract: Background. Environmental enrichment (EE) defined as "a combination of complex inanimate and social stimulation" influences brain function and anatomy by enhancing sensory, cognitive, motor, and social stimulation. The beneficial effects of EE in the presence of brain damage have been partially attributed to upregulation of neurotrophins, proteins involved in neuronal survival and in activity-dependent plasticity. Objective. The authors tested the hypothesis that EE may have advantageous effects on recovery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 59 publications
1
40
0
2
Order By: Relevance
“…Its potential involvement in PD is supported by the fact that PD patients are characterized by low levels of circulating BDNF (Scalzo et al 2010) and antiparkinsonian drugs may increase these levels in PD mouse models (Gyárfás et al 2010). Moreover, similar treatments, such as physical exercise as well as environmental enrichment, may upregulate BDNF in the brain (Gelfo et al 2011;Kleim et al 2003) and confer resistance to neurodegeneration in PD rodent models (Lau et al 2011). Nonetheless, the fact that BDNF increase is not sustained over time suggests caution on the possibility that beneficial effects of a rehabilitation program are associated with changes in BDNF neuronal synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its potential involvement in PD is supported by the fact that PD patients are characterized by low levels of circulating BDNF (Scalzo et al 2010) and antiparkinsonian drugs may increase these levels in PD mouse models (Gyárfás et al 2010). Moreover, similar treatments, such as physical exercise as well as environmental enrichment, may upregulate BDNF in the brain (Gelfo et al 2011;Kleim et al 2003) and confer resistance to neurodegeneration in PD rodent models (Lau et al 2011). Nonetheless, the fact that BDNF increase is not sustained over time suggests caution on the possibility that beneficial effects of a rehabilitation program are associated with changes in BDNF neuronal synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, parallel treatments in animal models, such as physical exercise and environmental enrichment, may upregulate members of the neurotrophic factor family, including brain-derived neurotrophic factor (BDNF) (Bekinschtein et al 2011;Gelfo et al 2011). and glial cell-derived neurotrophic factor (GDNF) (McCullough et al .2013).…”
Section: Introductionmentioning
confidence: 99%
“…These beneficial effects of EE in the presence of brain damage have been partially attributed to up regulation of neurotrophins, proteins involved in neuronal survival and in activity-dependent plasticity. Several studies showed that EE improves motor functions and increases levels of different neurotrophins after neurological disorders like hemicerebellar lesion, stroke, ischemia, etc., (Gelfo et al 2010;Söderström et al 2009). The findings of this study are in agreement with these observations.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the cellular and molecular pathways related to neuroprotection, it has been reported that enriched environment (EE) induces members of the neurotrophin family, especially brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF), a possible modulator of neuronal survival and plasticity (Rossi et al 2006;Lee and Paffenbarger 1998;Gelfo et al 2010). Almli and colleagues in their study demonstrated that intracerebroventricular BDNF pretreatment resulted in significant protection against hypoxia-ischemia (HI) induced histological injury and spatial memory impairments (Almli et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, morphological changes were found in the MSn of enriched animals following striatal damage [26][27][28]. Furthermore, in the presence of a cerebellar lesion, exposure to an enriched environment can mitigate motor symptoms of cerebellar origin [29][30][31]. Therefore, we assessed whether the adaptive morphological changes of Fsi elicited by HCb would be modulated by the exposure to an enriched environment after a cerebellar lesion.…”
Section: Introductionmentioning
confidence: 99%